(untitled) (CHORNOMORSKI BOTANICAL JOURNAL, 2026)
Question: What is the diversity and role of terrestrial algae, bryophytes and lichens in the initial stages of overgrowth of the former Kakhovka Reservoir bed, in particular, in the formation of soil biocrusts and corticolous biofilms? Location: Kakhovka Reservoir, Dnipropetrovsk, Kherson and Zaporizhzhia regions, Ukraine. Materials and methods: field and laboratory methods of collection and investiga-tion of algae, bryophytes and lichens, direct microscopy and culture methods (Kostikov et al. 2001, Bischoff & Bold 1963, Stanier et al. 1971) Nomenclature: algae and cyanobacteria (Guiry & Guiry 2026), bryophytes (Virchenko & Nyporko 2022), lichens (https://www.indexfungorum.org/) Results: During a three-year study of the exposed bed of the former Kakhovka Res-ervoir (2023-2025), 55 species of terrestrial algae (Cyanobacteria – 17 species, Chlorophyta – 27, Charophyta – 4, Heterokontophyta – 7), 2 species of bryophytes (Marchantia polymorpha and Funaria hygrometrica) and 1 species of lichen (Physcia adscendens) were identified. 50 algal species were found in soil biocrusts. Cyanobacteria and Chlorophyta were the most numerous there, dominating species were Phormidium takyricum, Chlorosarcinopsis cf. aggregata, Stenomitos sp., Microcoleus vaginatus, Klebsormidium cf. flaccidum, etc. On takyr-like (silt) substrates, 30 species of algae were found. Here, in a young willow-poplar forest, the liverwort Marchantia polymorpha was occasionally observed. A greater diversity of algae was found on sands: 36 species. Biocrusts dominated by the moss Funaria hygrometrica were often recorded on sands. 10 species of algae were recorded within the biofilms on willow bark, with green algae prevailing and Chloroidium cf. ellipsoideum as the dominant species. Additionally, the first epiphytic lichen (Physcia adscendens) was recorded at the same substrate. Conclusions: High cyanobacterial diversity of and their dominance in communi-ties are characteristic for soils in the steppe zone of Ukraine. A distinctive feature of biocrusts on silt is the predominance of fine-filamentous cyanobacteria. Biocrusts on sand were characterized by a higher diversity of algae and the occur-rence of aquatic species due to the periodic flooding of these areas. During the three years following the dam destruction, algal diversity in the biocrusts increased considerably. The low species richness in willow bark biofilms and the dominance of green algae are characteristic of aerophytic bark communities in the temperate zone. In the early successional stages of biodiversity recovery, bryophytes and lichens contribute minimally to the development of soil biocrusts and corticolous assemblages of willow trees.